Control of microstructure and mechanical properties of laser solid formed Inconel 718 superalloy by electromagnetic stirring. (1st February 2018) - Liu, Fencheng; Cheng, Hongmao; Yu, Xiaobin; Yang, Guang; Huang, Chunping; Lin, Xin; Chen, Jing
Highlights: EMS has an obvious effect on modify the microstructure of LSFed Inconel 718 superalloy. The residual stress distribution is proved to be much more uniform for the EMS. Tensile and high cycle fatigue of the LSFed Inconel 718 sample were enhanced after EMS. Abstract: The coarse columnar grains and special interface in laser solid formed (LSFed) Inconel 718 superalloy workpieces seriously affect their mechanical properties. To improve the microstructure and mechanical properties of LSFed Inconel 718 superalloy, electromagnetic stirring (EMS) was introduced to alter the solidification process of the molten pool during LSF. The results show that EMS could not completely eliminate the epitaxially growing columnar grains, however, the strong convection of liquid metals can effectively influence the solid–liquid interface growing mode. The segregation of alloying elements on the front of solid–liquid interface is inhibited and the degree of constitutional supercooling decreases correspondingly. Comparing the microstructures of samples formed under different process parameters, the size and amount of the γ+Laves eutectic phases formed in interdendritic area decrease along with the increasing magnetic field intensity, resulting in more uniformly distributed alloying elements. The residual stress distribution is proved to be more uniform, which is beneficial to the grain refinement after recrystallilzaiton. Mechanical properties testing results show an improvement of 100 MPa in tensile strength and 22% in elongation was obtained after EMS was used. The high cycle fatigue properties at room temperature was also improved from 4.09 × 10 4 cycles to 8.21 × 10 4 cycles for the as-deposited samples, and from 5.45 × 10 4 cycles to 12.73 × 10 4 cycles for the heat treated samples respectively.